2020
DOI: 10.1186/s13059-020-01998-1
|View full text |Cite
|
Sign up to set email alerts
|

Wheat chromatin architecture is organized in genome territories and transcription factories

Abstract: Background: Polyploidy is ubiquitous in eukaryotic plant and fungal lineages, and it leads to the coexistence of several copies of similar or related genomes in one nucleus. In plants, polyploidy is considered a major factor in successful domestication. However, polyploidy challenges chromosome folding architecture in the nucleus to establish functional structures. Results: We examine the hexaploid wheat nuclear architecture by integrating RNA-seq, ChIP-seq, ATAC-seq, Hi-C, and Hi-ChIP data. Our results highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
148
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(161 citation statements)
references
References 99 publications
13
148
0
Order By: Relevance
“…A similar two diagonal pattern was also reported for barley [ 27 ] and reflects the Rabl configuration [ 28 ], in which chromosomes fold back with centromeres and telomeres clustering at the opposite sides of the nucleus, leading to the adjacency of long and short arms. These results are consistent with the findings of earlier cytological studies [ 28 , 29 ] and recent Hi-C report in CS [ 3 ].
Fig.
…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…A similar two diagonal pattern was also reported for barley [ 27 ] and reflects the Rabl configuration [ 28 ], in which chromosomes fold back with centromeres and telomeres clustering at the opposite sides of the nucleus, leading to the adjacency of long and short arms. These results are consistent with the findings of earlier cytological studies [ 28 , 29 ] and recent Hi-C report in CS [ 3 ].
Fig.
…”
Section: Resultssupporting
confidence: 94%
“…The resulting tetraploid wheat hybridized with goatgrass ( Aegilops tauschii ; DD, 2n = 2x = 14) to produce an ancestral hexaploid wheat species approximately 10,000 years ago. In previous studies, genomic in situ hybridization (GISH) and Hi-C data revealed that the three subgenomes of hexaploid wheat tend to localize to specific nuclear territories [ 3 5 ]. Additionally, interactions are more common between subgenomes A and B than between subgenomes A and D or B and D. These findings indicate that the higher-order chromosomal organization may be maintained following tetraploidization and hexaploidization processes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wheat group offers an ideal system to study the evolution of polyploidy due to the ability to conduct comparative analyses between available species with different ploidy levels and since newly formed wheat allopolyploids can be easily produced in the greenhouse (Li et al, 2018). In light of the recent developments in wheat genomics, the examination of new models based on whole genome sequencing, epigenetic, and 3D analysis (Concia et al, 2020) is now technically possible for newly synthesized allopolyploids. Studies of TE dynamics in newly synthesized wheat allopolyploids might deepen our understanding of the effect of perturbation on host: TE dynamics (Roessler et al, 2018) and on the possible effect of the 3D genome organization on TEs insertion sites and propagation across the nucleus (Bousios et al, 2020).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…An extended synthesis framework should also be considered to understand domestication, as these new studies are helping us understand niche construction and the emergence of domesticated phenotypes (Piperno, 2017). Other potential lines of work remain to be addressed in domestication studies, such as the changes in the chromatin architecture (e.g., Concia et al, 2020), the use of comparative proteomic atlases (e.g., Jiang Y. et al, 2019) and the analysis of cell-type divergences during development using single-cell RNA-seq data (Arendt et al, 2016). The use of this multi-omic approaches will help us create and compare developmental atlases (e.g., Walley et al, 2016) between wild and domesticated taxa to understand how morphology diverged during domestication.…”
Section: Discussionmentioning
confidence: 99%